Zum politischen Programm der "Grenzboten" unter G. Freytags und J. Schmidts Redaktion (1847-1870). Mit bibliographischem Anhang der "polnischen Beiträge" für die Jahre 1845-1889 - Papiór, Jan (Studia Germanica Posnaniensia, 2018)
„Die Grenzboten“ magazine (founded by Ignaz Kuranda in Brussels in 1848) was one of the longest-appearing magazines of the German-speaking territory. While edited by Gustav Freytag and J. Schmidt, the magazine became the exponent of the anti-Polish policy. The political programme was realized not only by means of one-sided selection of the texts, but also by the anti-Austrian editing policy. Apart from literary texts, , Die Grenzboten“ contained mostly political and publicistic articles. The editorial board investigated the phenomena of the Polish-German cultural relationships as well as the border events. The enclosed bibliography of the so-called „Polish subjects“ gives an idea of the political programme of the editorial board and of the methods of awakening of the German nationalistic consciousness.